South African adolescent mothers' experiences of parenting and representations of their infants and the relationship between them. - Yates, Julianne (My University, 2013)
This study aimed to investigate teenage mothers’ experiences of motherhood and their internal representations of their infants and the relationship between them. In addition, this study aimed to investigate whether there was a connection between teenage mothers’ experiences of parenting and their internal representations of their infants and the relationship between them. Through the use of semi-structured interviews, adapted from the Parent Development Interview and the Working Model of the Child Interview, four teenage mothers from Alexandra were interviewed. The data collected from these interviews was analysed using narrative analysis through the hermeneutic lens of psychoanalytic attachment theory. From the analysis, this study found that teenage mother’s experiences of motherhood were marked by challenge. The two main challenges faced by these young mothers were the tension they experienced between their identities as teenagers and their identities as mothers, and their struggle to provide for their infants and feel like good enough mothers. In addition, this study found that teenage mother’s internal representations of their infants included a representation of both the good baby and the bad baby, but, with the exception of one mother, their representations tended to remain split and the mothers seemed defended against their representations of the bad baby. In terms of their representations of the relationship between them, this study found that these teenage mothers’ representations of their relationship with their infants was lacking. These representations either consisted of a superficial representation of a good relationship between mother and infant, or no relationship at all. Finally, this study found that teenage mother’s experiences of motherhood and their internal representations of their infants and the relationship between them were connected. A number of factors that were found to influence both their experiences and their internal representations include their own mental states, their memoires of their own childhood and their representations of their caregivers, as well as the levels of social support they received. The study therefore concluded that teenage mothers’ experiences of motherhood and their internal representations of their infants and the relationship between them were connected, however further research is required to establish the causal relationship between these factors.
Keywords: Teenage mothers--South Africa.; Mother and infant--South Africa--Psychological aspects.